Sistem Informasi Cargo Documentation Gudang Finished Goods Divisi Wafer PT.Mayora Indah Tbk - Giandari Maulani; Era Era Hia; Geri Yansyah (UNIVERSITAS RAHARJA, 2021)
PT. Mayora Indah Tbk is a company engaged in the industry that produces food and beverage products, warehouse wafer division which is one of the places to store, or arrange stock of goods from the production, or activities for the management of incoming and outgoing goods needed control in its movement activities. The current process on the documentation of goods cargo often occurs input errors no. police or truck containers, the use of mobile phone memory storage for photo files, convoluted processes, prone to loss of photo evidence files, difficulty finding data evidence files if there are complaints from the expedition, as well as on employees checkers and helpers do not know the history of the data report. Therefore, a web-based application system is needed to facilitate the search of photo data if there are complaints from the expedition, neat and regular storage of photo data, and for all employees to know the history and report of the photo data. To build this application using data collection methods namely observation, interviews and library studies, analysis methods using PIECES, system design using UML (Unified Modeling Language), and testing using Black Box Testing, while the programming language used is PHP with sublime text editor, as well as for databases using MySQL. With this system for the photo documentation process facilitates the ongoing process, and the management of data reports more regularly.